Women drug traffickers : mules, bosses, and organized crime - Carey, Elaine, 1967- (Diálogos (Albuquerque, N.M.), 2014)
In the flow of drugs to the United States from Latin America, women have always played key but rarely acknowledged roles as bosses, business partners, money launderers, confidantes, and couriers. Using international diplomatic documents, trial transcripts, medical and public welfare studies, correspondence between drug czars, and prison and hospital records as research the author brings to life women drug smugglers in the early twentieth century as well as the cartel queens who make news today.